2016
DOI: 10.1016/j.nlm.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Pedunculopontine tegmental nucleus lesions impair probabilistic reversal learning by reducing sensitivity to positive reward feedback

Abstract: Recent findings indicate that pedunculopontine tegmental nucleus (PPTg) neurons encode reward-related information that is context-dependent. This information is critical for behavioral flexibility when reward outcomes change signaling a shift in response patterns should occur. The present experiment investigated whether NMDA lesions of the PPTg affects the acquisition and/or reversal learning of a spatial discrimination using probabilistic reinforcement. Male Long-Evans rats received a bilateral infusion of NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…However, past studies have shown that a rat which has prior exposure to a working memory test or a different maze environment does not affect pharmacological or brain manipulations on behavioral flexibility tests compared to rats who have not had exposure to a working memory test or a different maze environment (DeCoteau & Kesner, 2000; Gilbert et al, 2001; Ragozzino et al, 1998, 1999, 2002). Similarly, acquisition performance in rats from the current study was comparable to that of rats that had not been previously exposed to a spontaneous alternation test (Brown et al, 2012; Syed et al, 2016). Thus, it is unlikely that exploring a maze in a different context influences subsequent spatial discrimination testing.…”
Section: Discussionsupporting
confidence: 63%
“…However, past studies have shown that a rat which has prior exposure to a working memory test or a different maze environment does not affect pharmacological or brain manipulations on behavioral flexibility tests compared to rats who have not had exposure to a working memory test or a different maze environment (DeCoteau & Kesner, 2000; Gilbert et al, 2001; Ragozzino et al, 1998, 1999, 2002). Similarly, acquisition performance in rats from the current study was comparable to that of rats that had not been previously exposed to a spontaneous alternation test (Brown et al, 2012; Syed et al, 2016). Thus, it is unlikely that exploring a maze in a different context influences subsequent spatial discrimination testing.…”
Section: Discussionsupporting
confidence: 63%
“…In line with our findings, the role of the PPN in adaptive behavior and action control has been previously addressed by a series of experiments using lesions or pharmacological manipulations. For example, non-specific PPN lesions impair adaptation to incremental walking speeds in a motor task 67 , affect the assimilation of new strategies with a consequent increase in perseverant responses 36,68 , and decrease the sensitivity to reward omissions 69 , thus denoting a failure in adjusting the behavioral state. Furthermore, pharmacological inhibition of the PPN produces a decrease in the responsiveness to degradation in contingencies between action and outcome, but did not change it if contingencies remain unchanged 70 , in line with findings showing impaired ability of rats to adapt to new strategies when the contingencies changed following inhibition of cholinergic transmission in the striatum 4,71 or CINs lesions 72 .…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, the role of the PPN in adaptive behavior and action control has been previously addressed by a series of experiments using lesions or pharmacological manipulations. For example, non-specific PPN lesions impair adaptation to incremental walking speeds in a motor task 64 , affect assimilation of new strategies with a consequent increase in perseverant responses 65,66 , and decrease the sensitivity to reward omissions 67 , thus denoting a failure in adjusting the behavioral state. Furthermore, pharmacological inhibition of the PPN produces a decrease in the responsiveness to degradation in contingencies between action and outcome, but did not change it if contingencies remain unchanged 68 , in line with findings showing impaired ability of rats to adapt to new strategies when the contingencies changed following inhibition of cholinergic transmission in the striatum 6,69 or CINs lesions 70 .…”
Section: Discussionmentioning
confidence: 99%